Changes in lung perfusion scintigraphy and pulmonary function tests in irradiated breast cancer patients - Ozlem Elmas; Rabiye Uslu Erdemir; Bekir Hakan Bakkal (Journal of the Pakistan Medical Association, 2021)
Objectives: To investigate the utility of quantitative lung perfusion scintigraphy and pulmonary function tests (PFTs) in the assessment of radiation-induced lung injury. Methods: Forty-three breast cancer patients underwent lung perfusion scintigraphy with Tc-99m macroaggregated albumin before and after radiotherapy (RT). Along with above mentioned tests pulmonary function tests and carbon monoxide diffusing capacity (DLCO) tests were carried out on all patients. The relationship between treatment related changes and its association with doses of RT were also analyzed. Results: DLCO values before RT showed a significant decrease at 6 and 12 months after RT (p=0.002 and p=0.004, respectively), while none of the parameters of the PFTs showed a significant difference before and after RT. Also, the median percentage of perfusion studies in the irradiated lung significantly decreased from 51.61% to 48.81% (p <0.001) at 12 months after treatment. There was significant reduction in perfusion studies of irradiated lungs with V20>20%. Conclusion: DLCO and Quantitative lung perfusion scintigraphy may be a useful tool for the early diagnosis and monitoring of radiation-induced lung injury. Continuous....